2012
DOI: 10.1002/macp.201200297
|View full text |Cite
|
Sign up to set email alerts
|

Droplet‐in‐Droplet Polymer Blend Microstructures: a Potential Route Toward the Recycling of Co‐mingled Plastics

Abstract: The problem of recycling co‐mingled plastics is primarily related to the problem of multiple interfaces in multicomponent immiscible polymer blends. Here, we study a new concept where thermodynamically driven polymer segregation and phase encapsulation are used to locate multiple phases within one of two major phases. Starting from a co‐continuous blend of HDPE and PP, hierarchically encapsulated PS/PMMA/PC composite droplets are found to be exclusively located within PP when the principal HDPE/PP interface is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…8,9 They can even be used as an approach to recycling co-mingled waste plastics. 10 A variety of phase morphologies can be obtained, in multiphase polymer blends, which offers the possibility to tune the properties of the resulting material. 11−26 For example, in ternary blends composed of two principal phases (A and B) and one minor phase (C), four types of morphologies are possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 They can even be used as an approach to recycling co-mingled waste plastics. 10 A variety of phase morphologies can be obtained, in multiphase polymer blends, which offers the possibility to tune the properties of the resulting material. 11−26 For example, in ternary blends composed of two principal phases (A and B) and one minor phase (C), four types of morphologies are possible.…”
Section: Introductionmentioning
confidence: 99%
“…Several parameters play a role in determining the obtained morphology, both related to the polymer themselves (i.e., composition, viscosity ratio, and interfacial tension) or to processing (thermomechanical history of the sample). Recently, considerable attention has been paid to multicomponent polymer blends, comprising at least three immiscible polymers. Such systems can result in a set of entirely new materials, such as high-performance bioplastics, , hierarchically porous polymers, , and conductive polymer blends with ultra-low percolation thresholds. , They can even be used as an approach to recycling co-mingled waste plastics …”
Section: Introductionmentioning
confidence: 99%
“…However, controlling the morphology and microstructure of the blend is essential to achieve the desired properties 3,12,15,24 . By increasing the number of components, controlling the morphology and properties of blends become very challenging 25–28 …”
Section: Introductionmentioning
confidence: 99%
“…The critical role of interfacial tension in controlling morphology in completely wet ternary polymeric systems has also been reported in several studies. 4,10,20 The addition of a small amount of interfacial modifier to an HDPE/PS/PP system modified the morphology from composite droplets of PS encapsulated by PP to separately dispersed PS and PP droplets in the matrix of HDPE. 4 Wilkinson et al 21 observed a morphology transition from separately dispersed phases of PA6 and poly[styrene-b-(ethylene-co-butylene)-b-styrene] (SEBS) triblock copolymer to partially and then finally completely engulfed PA6 droplets upon the progressive replacement of SEBS with a reactive maleic anhydride-grafted SEBS-g-MA in a matrix of PP.…”
Section: Introductionmentioning
confidence: 99%